Erratum: Perbandingan Sport Massage dan Hydrotherapy Cold Water Terhadap Physiological Recovery - Hawin Fahmi; Kunjung Ashadi (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.566 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.